Marine shelled Heterobranchia in part (Gastropoda) of the Miocene Central Paratethys Sea - Harzhauser, Mathias; Landau, Bernard M.; Malaquias, Manuel António E. (Zootaxa, 2026)
We present a revision of the Early and Middle Miocene marine heterobranchs from the European Central Paratethys Sea. We document a surprisingly high diversity of 83 species of which 32 species are described as new species. As shown by many other gastropod families, discussed in previous papers of this series, maximum diversity occurred during the middle Badenian, 65 species, corresponding to the Miocene Climatic Optimum. The extant Indo-West Pacific genus Vellicolla Oskars, Too, Rees, Mikkelsen, Willassen & Malaquias, 2019 is recorded for the first time from the Miocene of the Circum-Mediterranean Region. Following species are described as new: Acteon antipinguis sp. nov., Acteon gutta sp. nov., Acteon romanicus sp. nov., Acteon trifasciatus sp. nov., Acteon viciani sp. nov., Acteon vindobonensis sp. nov., Rictaxis austriacus sp. nov., Rictaxis siedli sp. nov., Rictaxis ursulae sp. nov. (Acteonidae), Ringicula daisyae sp. nov. (Ringiculidae), Bulla? elalbanii sp. nov. (Bullidae), Pyrunculus microromanicus sp. nov., Pyrunculus szobiensis sp. nov., Pyrunculus zuschini sp. nov., Retusa mystica sp. nov. (Retusidae), Cylichna caudex sp. nov., Cylichna dolium sp. nov., Cylichna eschnerae sp. nov., Cylichna miosimplex sp. nov., Cylichna steiningeri sp. nov., Cylichna straussi sp. nov. (Cylichnidae), Chelidonura piseraii sp. nov. (Aglajidae), Roxania oviformis sp. nov., Roxania pila sp. nov. (Alacuppidae), Sabatia quasimodoi sp. nov., Scaphander alatissimus sp. nov., Scaphander catena sp. nov., Scaphander perforatus sp. nov., Scaphander quadratus sp. nov., Scaphander schollnbergeri sp. nov. (Scaphandridae), and Pseudavena bella sp. nov. (incertae sedis). Acrostemma anatolica sp. nov. (Cylichnidae) is described from the Middle Miocene of Turkey. Neubaueriella nov. gen. (Haminoeidae) is introduced as new genus. Roxania bomba nov. nom. is introduced as new name for the secondary homonym Roxania helvetica (Berger, 1949) non Roxania helvetica Peyrot, 1932.